SAT0443 The impact of musculoskeletal conditions across europe: Availability of routinely collected data. The eumusc.net project. (23rd January 2014) - Woolf, A.D.; Erwin, J.; Carmona, L.
Abstract : Background: EUMUSC.NET is a 3 year project to raise and harmonise the equity and quality of care for MSC across the 27 EU Member States. A key aim is to raise the profile of MSC among policy makers. EUMUSC.NET reviewed the data available to evidence the impact of MSC nationally and across the EU in terms of health, social, employment and economic measures. Objectives: To identify comparable data from individual Member States to evidence the health, social, employment and economic impact of MSC on the EU. Methods: National health survey co-ordinators and national statistical office representatives in each Member State were contacted to identify the availability of relevant data. European and international sources of MSC related data were identified and country experts consulted. Data was obtained from these sources. Results: Incidence and prevalence data is available largely from research studies and health interview surveys. The availability of data is very variable with a lack of epidemiological data for Central, Eastern European and some Mediterranean countries; the European Health Interview Survey (EHIS) which has good up take-up in these States provides self reported data on some conditions. Primary and community health services utilisation data is not included in European level indicators and is available only through national sources. Indicators of hospital services utilisation is collected by the OECD and WHO and includes MSC related hospital admissons, average length of stay, day cases and number of surgeries. Self reported data on the use of medication for MSC is available from the EHIS and the adhoc Eurobarometer survey. The OECD Health database includes data from national medicine sales registers on drugs for the musculoskeletal system; different countries have are a number of sources of undereporting. Data on the number of rheumatology physicians is collected by EUROSTAT. Human resources data from professional groups vary in definitions and completeness of records. Health related quality of life data is largely restricted to research studies; little data is comparable between Member States. The Global Burden of Disease programme produce MSC related Disability Adjusted Life Years and Years Lived with Disability WHO have data on MSC related mortality. Data on temporary and permanent work loss related to MSC is collected in ad hoc surveys and national statistics but not routinely for the EU27. Ad hoc surveys and modules do not allow secular tends to be explored. National statistics tend to lack details of diagnosis and are restricted to particular population groups. Conclusions: Recognising the impact of MSC is key to the argument for prioritising MSC prevention, manangement and research. The true impact of MSC can only be measured if there is robust data. There is a severe lack of up to date data on MSC which is comparable across EU Member States. One striking finding given its potential policy impact is the lack of comparable data on MSC related work loss and sickess absence. The new revised version of EHIS has less MSC related questions and so misses an opportunity to provide comparable data on these important conditions. If the goal of raising the priority of MSC is to be achieved there is an urgent need for improved sources of routine data on MSC within and across the EU Member States. Disclosure of Interest: None Declared